Physiological-metabolic variables of heat stress in cows grazing in silvopastoral systems and in one treeless prairie. - Berragán-Hernández, Wilson Andrés; Mahecha-Ledesma, Liliana; Cajas-Jirón, Yasmin Socorro (Agronomía Mesoamericana, 2015)
The aim of this work was to analyze changes of physiological and metabolic parameters as indicators of heat stress of cows in pasture systems. The research was carried out from 2011 to 2012 at the Turipaná Agricultural Research Center of Corpoica located in the Caribbean region in Cereté–Colombia. Environmental temperature (T) and relative humidity (H) were determined, as well as and rectal temperature (RT), skin temperature (ST), respiratory frequency (RF) and the acid-basic status of animals. The variables were measured in the morning (6:00 h) and in the afternoon (13:00 h). Significant Statistical differences were observed (p<0.05) in environmental temperature treatments (T) with 7% and 6% less temperature in p-Arbus-Arbor y p-Arbor, respectively, compared with grass treatment. There was a significant hour effect on T and H (p<0.05) and a significant treatment-hour interaction on T (p<0.05). TP and FR showed a significant treatment-hour interaction per hour (6:00/13:00 h). The results show a positive effect of shadow from trees on the physiological variables. The negative effects observed on the physiological variables of unshaded treatments impacted in a minimal way the metabolic variables suggesting homeostatic responses in the animals under the evaluated stressful environmental conditions.